K.H. Sholeh Darat’s Hadith Understanding In Majmū’ah Al-Sharī’ah Al-Kaifiyah Lil Al-Awwām Book - Rohmansyah Rohmansyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article aims to explain the understanding of K.H. Sholeh Darat in the Majmū'ah al-Syarī'ah al-Kaifiyah lil Awwām book by looking at the social context that occurred in the past when the hadith was delivered. This paper uses a descriptive-analytical method with a sociological-historical approach and syarh hadith. The findings show that K.H. Sholeh Darat is an ulama from Java who was present in the midst of a society is closely related with the traditions of a plural society both santri, priyai and abangan. He tends to understand the hadith textually under certain conditions, but on the other hand it tends to be contextual depending on the situation and environmental conditions he experiences or ṣāliḥun li kulli zamānin wa makānin. Besides, it is undeniable that the understanding is less from the methodology of hadith understanding that was initiated by contemporary hadith experts such as textual understanding of tasyabbuh hadith and hadith of pilgrimage to the Prophet's tomb. However, he understands the hadith about intercession contextually